HUMAN RIGHTS WITHOUT BORDERS: ILLEGAL MIGRATION, HUMAN TRAFFICKING AND THE DIGITAL REALITY IN THE CONTEXT OF GLOBALIZATION AND THE DIGITAL ENVIRONMENT (Ustozlar uchun, 2025)
The processes of globalization and the rapid development of digital technologies have elevated the protection of human rights to a new level; however, they have also contributed to the rise of transnational threats such as illegal migration and human trafficking. Legal gaps that emerge during irregular migration, strict border controls, and undocumented movement expose individuals to serious risks of exploitation. Human trafficking, involving coercion, deception, violence, or the abuse of vulnerability, remains one of the most severe crimes, and the expanding digital environment has further broadened its scope. The internet and social networks have become primary tools for luring people into exploitation networks through fraud, false job offers, and misinformation about migration routes. At the same time, digital footprints, video, and photographic documentation serve as important sources for identifying human rights violations.